Chimeric Antigen Receptor, Teamwork, Education, Assessment, and Management (CAR-TEAM): A Simulation-Based Inter-professional Education (IPE) Intervention for Management of CAR Toxicities - Harden, Avis; Ragoonanan, Dristhi; Anildes-Gubman, Daryl; McCall, David; Faltus, Kathleen; Featherston, Sarah; Shoberu, Basirat; Moffet, Jerelyn R.; Petropoulos, Demetrios; Khazal, Sajad J.; Razvi, Shehla; Mahadeo, Kris M.; et al. (Frontiers in Oncology, 2020)
Chimeric antigen receptor (CAR) therapies such as tisangelecuel, indicated for children and young adults with relapsed and/or refractory CD19+ acute lymphoblastic leukemia (ALL) have been associated with striking treatment outcomes and overall survival. Yet, they are also associated with unique and potentially life-threatening complications. Cytokine release syndrome (CRS) and immune effector cell associated neurotoxicity (ICANS) are generally reversible complications of CAR-therapies, but almost half of patients may require critical care support especially if they are not promptly recognized and appropriately managed by front-line healthcare staff. As CAR therapies become more widely available, it is important that inter-professional staff members be aware of general principles regarding diagnosis and management. We hypothesized that an inter-professional education (IPE) simulation based education intervention (CAR-TEAM) would improve knowledge base and confidence regarding complications of CAR therapies among inter-professional staff. Here, we demonstrate that following CAR-TEAM training > 90% of participants demonstrated knowledge proficiency and confidence in the IPE content area. CAR-TEAM training may serve as an important tool to establish initial and continued competency among sites introducing CAR therapies.